AGRICULTURAL SECTOR DEVELOPMENT WITHIN THE «UKRAINE FACILITY» PROGRAM - Konstantin Peychev (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. The agricultural sector has significant potential in Ukraine and can stimulate economic growth. In this direction, the key factors are further integration into the European Union.